Kesepian Pasca Putus Cinta pada Dewasa Awal: Menilik Pengaruh Self Compassion dan Dukungan Sosial - Anisa Priastuti Utami; Cempaka Putrie Dimala; Anggun Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Loneliness that arises after a breakup is an emotional challenge that is often experienced by early adult individuals who are in the stage of building emotional closeness. Self compassion plays a role in helping individuals deal with negative emotions adaptively, while social support is believed to reduce feelings of alienation. The research method used is quantitative with a causality approach. The research sample consisted of 385 respondents aged 18-30 years who were selected through purposive sampling technique. The measuring instruments used include the UCLA Loneliness scale, Self Compassion Scale (SCS), and Multidimensional Scale of Perceived Social Support (MSPSS). The results of partial hypothesis testing show that self compassion has an effect by getting a significance value of 0.000 on loneliness (p < 0.05), while social support shows no effect by getting a significance value of 0.085 (p < 0.05). The results of simultaneous hypothesis testing show that self compassion and social support have an effect with a significance value of 0.000 on loneliness (p < 0.05), with a contribution of 52.9%..